E Effect Alkaline Activator Ratio on Porosity Geopolymer Binder Based Umeanyar Slate Stone Powder - Astariani, Ni Kadek (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2021)
This research focuses on the manufacture of geopolymer binder based on Umeanyar slate stone powder (USSP) with alkaline activator sodium silicate (Na 2 SiO 3 ) and sodium hydroxide (NaOH). The effect of alkaline activator ratio on porosity was investigated in this study. USSP geopolymer binder contains SiO 2 (49%), Al 2 O 3 (11%), CaO (11.2%) and uses a NaOH activator with a concentration of 14 M. The proportion of precursor and activator (P/A) are 70%: 30%; 75%: 25%; 80%: 20% and alkaline activator Na 2 SiO 3 : NaOH (SS/SH) were 1: 1; 1.5: 1; 2: 1, by weight. The sample of the specimen is made in the mould of a cylinder with a diameter of 25mm and height of 50 mm and tested at the age of 7 and 28 days. Porosity test according to ASTMC642-06. The porosity test results of the geopolymer binder at the age of 28 days were decreased when the P/A ratio increased and the SS/SH ratio decreased.